Investigating the Performance of Second Language Medical Students on Lengthy Clinical Vignettes. (June 2017) - Raymond, Mark R.; Ling, Yu; Grabovsky, Irina
This study evaluated the extent to which medical students with limited English-language experience are differentially impacted by the additional reading load of test items consisting of long clinical vignettes. Participants included 25, 012 examinees who completed Step 2 of the U.S. Medical Licensing Examination®. Test items were categorized into five levels based on the number of words per item, and examinee scores at each level were evaluated as a function of English-language experience (English as a second language [ESL] status and scores on a test of English-speaking proficiency). The longest items were more difficult than the shortest items across all examinee groups, and examinees with more English-language experience scored higher than those with less experience across all five levels of word count. The effect of primary interest—the interaction of word count with English-language experience—was statistically significant, indicating that score declines for longer items were larger for examinees with less English-language experience; however, the magnitude of this interaction effect was barely detectable (η 2 = .0004, p < .001). Additional analyses supported the conclusion that the differential effect for examinees with less English-language experience was small but worthy of continued monitoring.